Pengaruh Penerapan Strategi Pembelajaran PQ4R Terhadap Keterampilan Membaca Siswa Kelas V SDN 04 Tala Kabupaten Pangkep - Ulfa Riyani; Aco Karumpa; Ummu Khaltsum (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The main problem in this study is the low absorption of students. This can be seen from the average student learning outcomes which are still a cause for concern. This study aims to determine the effect of implementing the PQ4R learning strategy on the reading skills of fifth grade students at SDN 04 Tala, Pangkep Regency. This type of research is an actual experimental research (true experiment). The population of this study were fifth grade students at SDN 04 Tala Pangkep Regency with a total of 26 students who were divided into 2 classes. The sample in this study, namely fifth grade students at SDN 04 Tala, consisted of 13 experimental class students and 13 control class students. The research design used was the Posttest Only Control Group Design. The results of this study indicate that the effect of the PQ4R learning strategy on students' reading skills. The average value of reading skills given action by applying PQ4R learning strategies (experimental class) is 8.76, while the average value of reading skills that are not given action by not implementing PQ4R learning strategies (control class) is 6. So, skills The reading comprehension of students who were given the PQ4R strategy action (experimental class) was higher at 8.76 than students who were not given the PQ4R strategy action (control class).